Examine factors that affect sports gambling among the youth: A case study of three suburbs of the Kumasi Metropolitan Assembly of the Ashanti Region of Ghana. - Baffour, Janet Antwi (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirement For The Degree Of Master Of Arts (MA) Sociology.